Cryptotanshinone protects skin cells from ultraviolet radiation-induced photoaging via its antioxidant effect and by reducing mitochondrial dysfunction and inhibiting apoptosis - Guo, Keke; Liu, Run; Jing, Rongrong; Wang, Lusheng; Li, Xuenan; Zhang, Kaini; Fu, Mengli; Ye, Jiabin; Hu, Zhenlin; Zhao, Wengang; Xu, Nuo (Frontiers in Pharmacology, 2022)
The integrity of skin tissue structure and function plays an important role in maintaining skin rejuvenation. Ultraviolet (UV) radiation is the main environmental factor that causes skin aging through photodamage of the skin tissue. Cryptotanshinone (CTS), an active ingredient mianly derived from the Salvia plants of Lamiaceae, has many pharmacological effects, such as anti-inflammatory, antioxidant and anti-tumor effects. In this study, we showed that CTS could ameliorate the photodamage induced by UV radiation in epidermal keratinocytes (HaCaT) and dermal fibroblasts (HFF-1) when applied to the cells before exposure to the radiation, effectively delaying the aging of the cells. CTS exerted its antiaging effect by reducing the level of reactive oxygen species (ROS) in the cells, attenuating DNA damage, activating the nuclear factor E2-related factor 2 (Nrf2) signaling pathway, and reduced mitochondrial dysfunction as well as inhibiting apoptosis. Further, CTS could promote mitochondrial biosynthesis in skin cells by activating the AMP-activated protein kinase (AMPK)/ sirtuin-1 (SIRT1)/ peroxisome proliferator-activated receptor-γ co-activator-1α (PGC-1α) signaling pathway. These findings demonstrated the protective effects of CTS against UV radiation-induced skin photoaging and provided a theoretical and experimental basis for the application of CTS as an anti-photodamage and anti-aging agent for the skin.